Study of Handloom Development Programme - Planning Commission (Planning Commission, 1967)
Till the advent of the machine age revolulionising the production of textile goods, the handloom industry in India was playing the most important role in the country's economy. It was and even now is the largest cottage industry of the country. Nearly a third of the total re quin mem of cloth is provided from this industry. India has a rich past in the handloom industry; the country used to export handloom textiles of excellent quality to Middle East and European Countries. With the growth of textile mills, the handloom industry started facing competition from them. the consumers' preference to mill-made cloth which was superior in quality for the price paid for. resulted in reduction of demand for handloom products. The mode of production of handloom cloth was old and outmoded; there was no effective organisation amongst the handloom weavers to lead them towards their economic rehabilitation and betterment. the need was thus felt to take adequate steps to put this industry back on sound economic fooling.
Programme Evaluation Organisation Planning Commission Government of India